Tissue-specific differences in DNA methylation in various mammals. - Gama-Sosa, M A; Midgett, R M; Slagel, V A; Githens, S; Kuo, K C; Gehrke, C W; Ehrlich, M (Biochim Biophys Acta, 1983)
The only naturally occurring modified base in vertebrate DNA is 5-methylcytosine. Using a precise high-performance liquid chromatographic analysis of DNA enzymatically digested to deoxynucleosides, we have shown that rats, mice and four types of monkey display tissue-specific as well as species-specific differences in the extent of methylation of their cytosine residues. Several similarities in the patterns of tissue-specific DNA methylation in these mammals and in the previously studied human samples were observed. Compared to most other types of DNA examined, brain and thymus DNAs were hypermethylated which suggests that this hypermethylation is a determinant or a necessary byproduct of mammalian differentiation. In all of the studied rodents and primates, the highly repeated DNA sequence fraction was more methylated than the moderately repetitive or single copy fractions. The tissue-specific differences in overall DNA methylation showed no correlation with what is known about average cell turnover rates nor with the percentage of the genome that is transcribed. Liver regeneration in the rat following partial hepatectomy did not detectably alter 5-methylcytosine levels in liver DNA. A considerable increase in the extent of methylation of total liver DNA was observed during normal development of the rat. The latter phenomenon may be due to a major change in the cellular composition of the liver.
Keywords: 5-Methylcytosine; Animals; Chromatography, High Pressure Liquid; Cytosine; DNA; Mammals; Methylation; Species Specificity; Tissue Distribution